Oliver Twist - Dickens, Charles (Pearson Education Limited, 1966)
With Oliver Twist his reputation was enhanced and strengthened.The novel contains many classic Dickensian themes- grinding poverty, desperation, fear, temptation and the eventual triumph of good in the face of great adversity.....
Keywords: Classics; Fiction; Criminals; Fiction; Literary; London (England); Orphans